2005
DOI: 10.1128/iai.73.6.3492-3501.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of theMycobacterium tuberculosisMmpL Protein Family to Virulence and Drug Resistance

Abstract: The genome sequence of Mycobacterium tuberculosis revealed the presence of 12 membrane proteins proposed to have a function in the transport of lipids. Insertional inactivation of 11 of these has revealed that only 1 (MmpL3) is apparently essential for viability. Five of these proteins are conserved within the genome of Mycobacterium leprae. The drug susceptibilities of these 11 mutants to a broad spectrum of agents are unaltered, suggesting that unlike their function in other organisms, these proteins do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
346
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(359 citation statements)
references
References 52 publications
10
346
2
1
Order By: Relevance
“…5 C and D). These results imply extracellular to intracellular heme transport and offer concrete support of the previous proposal that several MmpL proteins may be involved in mycobacterial metabolite import (32). The high sequence homology and close genomic proximity of MmpL3 and MmpL11 (and also the hemophore Rv0203), and the similar heme binding properties of their soluble domains, support roles of both MmpL3 and MmpL11 in heme uptake.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…5 C and D). These results imply extracellular to intracellular heme transport and offer concrete support of the previous proposal that several MmpL proteins may be involved in mycobacterial metabolite import (32). The high sequence homology and close genomic proximity of MmpL3 and MmpL11 (and also the hemophore Rv0203), and the similar heme binding properties of their soluble domains, support roles of both MmpL3 and MmpL11 in heme uptake.…”
Section: Resultssupporting
confidence: 67%
“…Thus, we postulate that MmpL11 and MmpL3 are both heme transporters. Previously, it was shown that mmpL3 is likely to be essential (32), and our attempts to delete the potential heme uptake region (Rv0201c-Rv0207c) or mmpL3 alone from MtbΔmbtB were also unsuccessful. To evaluate the involvement of MmpL11 in heme uptake, a double mutant with deleted Rv0202c (mmpL11) was constructed by replacing most of the mmpL11 coding region with an apramycin resistance cassette and its promoter in-frame (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This cell-wall-associated lipid is composed of a long-chain b-diol (phthiocerol) esterified to two multi-methyl branched fatty acids (mycocerosic acids). At least three independent studies have confirmed that M. tuberculosis mutants deficient in PDIM synthesis or translocation are severely attenuated in vivo (Camacho et al, 1999;Cox et al, 1999;Domenech et al, 2005). None of these studies have reported an in vitro defect associated with the loss of PDIM.…”
Section: Introductionmentioning
confidence: 74%
“…In each of these two studies, the level of in vivo attenuation afforded through the loss of PDIM was approximately 50-fold in mouse lungs by just 3 weeks post-infection. We have subsequently described the same level of attenuation for an MmpL7 mutant generated in H37Rv (Domenech et al, 2005). MmpL7 is the transmembrane transport protein necessary for PDIM export.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation